Complejo en turismo de aventura para la consolidación de una economía sostenible para la región del Sumapaz: plan parcial: Sakúku. Sibaté – Cundinamarca (2018)
After making a physical inventory within territorial scales of study, this, gave as a diagnosis. The lack of articulation of the great environmental element to the populations, and the mono-function, in which the economy develops, in addition, the advanced environmental deterioration caused by mining. and the noxious agriculture in the surroundings of páramo. Following this, a municipal urban area and a reservoir of Muña with a recovery projection to 2050 are proposed in accordance with the Regional and Sub-regional determinants. And a partial plan of the city border, to delimit the excessive growth, in addition, some projects on that urban edge, which are of regional impact and which go hand in hand with the recovery of the ecological structure of the municipality. At the level of the action unit, a development ofthe fairs square is planned, integrating it with the most important body of water, which is the Muña reservoir, thus, generating a point of high tourist affluence through different strategies of urban design, such as rainwater harvesting, tree systems, management of green and hard areas, and the interconnection of institutional buildings through pedestrian and vehicular axes. The project seeks as a complex of adventure and identity, to reinforce the sustainable economy in the region, based on the tourist model of the small entrepreneur, thus, generating a reference on how to exercise the service activity to the foreign population, using the municipality's advantages in sporting terms, as stipulated in the departmental tourist development plan. In addition, as an additional feature, reinforce the idea of the identity of the territory to promote its care.